Using Data Envelopment Analysis to Evaluate Environmentally Conscious Tourism Management - Valentina Bosetti; Mariaester Cassinelli; Alessandro Lanza (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper discusses a methodology to assess the performances of tourism management of local governments when economic and environmental aspects are considered as equally relevant. In particular, the focus is on the comparison and efficiency assessment of Italian municipalities located on the costal areas. In order to assess the efficiency status of the considered management units, Data Envelopment Analysis (DEA), a methodology for evaluating the relative efficiency of decision making units, is applied. The efficiency index measure used in DEA analysis accounts for both environmental and economic features correlated to the tourism industry. Further, potential managerial improvements for those areas resulting far from the efficiency frontier can be investigated.
Keywords: L83; M40; Q01; 330; Data envelopment analysis; Sustainable tourism; Tourismuspolitik; Umweltschutz; Data-Envelopment-Analyse; Italien